Nutritional anemia and its epidemiological correlates among women of reproductive age in an urban slum of Bhubaneswar, Orissa - Ansuman Panigrahi; Prasun Bikash Sahoo (Wolters Kluwer Medknow Publications, 2011)
The present cross-sectional study involving 240 women of reproductive age as the study population was carried out in the beneficiary slum area, the field practice area of Community Medicine department to find out the burden of nutritional anemia and study its epidemiological correlates. The prevalence of anemia was found to be 60.8%, of which 39.6, 20.0 and 1.2% women had mild, moderate and severe anemia, respectively. Almost 63, 21.2 and 15.7% of the study subjects had microcytic hypochromic picture, indicative of iron deficiency anemia, normocytic hypochromic picture suggestive of early stage of iron deficiency anemia and dimorphic/ macrocytic hypochromic anemia implying iron deficiency anemia and or folate/vitamin B12 deficiency respectively. Statistical analyses have shown that epidemiological factors like age, education of respondents, socioeconomic status, history of excessive menstrual bleeding and inadequate intake of green leafy vegetables and pulses were found to be significantly associated with anemia.